Pengaruh Fosfat Alam dan Kombinasi Bakteri Pelarut Fosfat dengan Pupuk Kandang terhadap P Tersedia dan Pertumbuhan Kedelai pada Ultisol - Aidi Noor (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2003)
The aims of this experiment were to evaluate the effect of rock phosphate application and combination phosphate- solubilizing bacteria and farm yard manure on soil available P and growth of soybean on Ultisol from Kentrong village, Banten province. Factorial experiment design with two factors was used in randomized complete block design ; with three replications. The first factor was rock phosphate i.e. : 0, 30, 60, and 90 kg Plha, and the second factor was ' combination of phosphate solubilizing bacteria (PSB) and farm yard manure (FYM) i.e. : without PSB and FYM (control), PSB (Pseudomonas fluorescens), FYM 10 t/ha, and PSB+FYM Results indicated that significant positive effect of rock phosphate and combination of PSB and FYM application occurred on soil available P, number and dry weight of nodule, dry weight of root and shoot. Rock phosphate application with rates of 30, 60, 90 kg P/ha increased soil available P 247%, 356% and 592% respectively compared 'to without P. Phosphate-solubilizing bacteria, farm yard manure and PSB+FYM increased 27%, 30% and 48% respectively compared to control. Phosphate-solubilizing bacteria and farm yard manure combination with phosphate rock 30 kg P/ha dosage increased dry weight of soybean shoot 29% compared to control. Key words: Rock phosphate, Phosphate-solubilizing bacteria, Farm yard manure; Soybean, Ultisols.